THE EFFECT OF CPO (CRUDE PALM OIL) PRICE ON FINANCIAL PERFORMANCE AND ITS IMPACT ON STOCK PRICES OF PALM OIL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2014–2024 - Ani Apriani; Muhammad Firmansyah (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2026)
Indonesia is the world's largest producer of crude palm oil (CPO). Global CPO price fluctuations do not always align with the financial performance of palm oil plantation companies. This study aims to analyze: (1) the effect of CPO price on financial performance (ROA) of palm oil companies; (2) the effect of financial performance (ROA) on stock prices; and (3) the mediating role of ROA in the relationship between CPO price and stock prices. A quantitative associative method was employed using balanced panel data from 9 palm oil companies listed on the Indonesia Stock Exchange (IDX) for the period 2014–2024 (99 observations). Panel data regression and Sobel test were conducted using EViews 12. Results show that: (1) CPO price has a significant positive effect on ROA at the 10% significance level (coefficient = 0.0584, p = 0.0504); (2) ROA has a significant positive effect on stock prices at the 5% level (coefficient = 1.499, p = 0.0282); (3) ROA has not been proven as a statistically significant mediator at the 5% level (Sobel statistic = 1.68), although a mediating tendency is observed at the 10% level. These findings suggest that rising CPO prices increase company profitability; however, the effect on stock prices through the profitability channel is limited due to time lag factors and the capital-intensive nature of the industry. This study recommends the necessity of strengthening operational efficiency and downstream diversification for firms, profitability-based fundamental analysis for investors, and government policies that focus not only on CPO price stability but also on downstream industry development and sustainability to ensure the long-term resilience of the palm oil sector.